Impact pathways of adverse childhood experiences on infectious diseases among substance abusers in border regions: structural equation modeling - Zhang, Mingmei; He, Jianhui; Young, J. Melvin; You, Jing; Li, Jing (Frontiers in Public Health, 2025)
BackgroundInjection of drug abuse could result in infectious disease, and adverse childhood experiences (ACEs) possibly are associated with infectious disease. However, there is a paucity of literature on a direct or indirect relationship between ACEs, injection of drug use and infectious disease. We thus identified the pathway of influence of ACEs in adulthoods and injection of drug use on infectious disease by structural equation models (SEM).MethodsA cross-sectional study was conducted by respondent driving sampling and consecutive sampling among people who use drugs in southwest of China in 2021. R software 4.2.1 was used to conduct descriptive, univariate, and SEM analysis.ResultsThere were 404 participants in total, with an average age of 34 and most males (98.3%) and minorities (79.6%). 95.5% of respondents experienced ACEs with 46.6% of reporting 4 or more ACEs. Correlations in SEM showed that infectious disease might be directly positively affected by injection of drug use (β = 0.184), and directly negatively affected by ACEs (β = −0.188). Age (β = 0.029), Ethnic (β = −0.021), Education (β = 0.019), Gender (β = 0.022), Sex partners (β = −0.017), and ACEs (β = −0.029) might have indirect effects on infectious disease.ConclusionACEs might be a direct or indirect predictor for infectious disease in adulthood, injection of drug use might be a risk factor and moderate other factors of infection of infectious disease. Strategies for creating a positive home environment, minimizing traumatic or stressful childhood experiences, and increasing awareness of the risks associated with drug injection use are all ways to lower the chances of contracting infectious diseases.